Infectious lung masses misdiagnosed as metastatic rhabdomyosarcoma: Two case reports. Issue 6 (24th January 2021) - Jian, Binglin; Xu, Na; Duan, Chao; Zhao, Wen; Su, Yan; Yu, Tong; Fu, Libing; Chen, Chenghao; Zeng, Qi; Ma, Xiaoli
Summary: Rhabdomyosarcoma (RMS) with regional lymph node involvement has a high rate of distant metastases. Lung is the most common site, accounting for 70% of all metastases. The differential diagnosis of lung lesions due to an infectious aetiology versus metastases is usually evaluated by computed tomography (CT) or magnetic resonance imaging. However, it is rare for patients of RMS to present with infectious nodules or masses in the lung during follow‐up. More importantly, infections can mimic the imaging characteristics of metastatic RMS in CT. We report two such cases where children diagnosed with head and neck embryonal RMS with lymph node metastasis, presented with pulmonary masses 0.5 and 4 years after end of treatment, without the typical signs and symptoms suggestive of an infection. Chest CT suggested a provisional diagnosis of metastases and biopsies confirmed infectious aetiology ( Mycobacterium tuberculosis, Cryptococcus ).